Sistem Pemantauan Suhu dan Kelembapan Kandang Ayam Berbasis IoT dengan Notifikasi Telegram Otomatis - Nayoan, Vallen Ezra Piter; Arinal, Veri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This research focuses on the design and implementation of a chicken coop temperature and humidity monitoring system based on the Internet of Things (IoT) with automatic notifications through Telegram. The study was motivated by the problems faced by poultry farmers, particularly the difficulty of continuously monitoring environmental conditions manually and the lack of an early warning system when temperature or humidity exceeds the normal threshold. The proposed system integrates a DHT22 sensor to measure temperature and humidity, a NodeMCU ESP8266 microcontroller to process data and connect to Wi-Fi, and the Telegram Bot API to deliver automatic notifications. The prototype was developed using a prototyping methodology, including design, implementation, and testing stages. The test results demonstrate that the DHT22 sensor provided sufficient accuracy with an average error of ±0.3°C for temperature and ±1%RH for humidity. Notifications via Telegram were successfully delivered within 3–5 seconds after critical conditions were detected. Additionally, the system applies a 10-minute delay for normal conditions to avoid message spamming while still ensuring continuous monitoring. Overall, the system effectively supports poultry farmers by enabling real-time monitoring, early warnings, and efficient management of coop environmental conditions. This prototype highlights the potential of IoT-based solutions to modernize poultry farming and increase productivity through practical and cost-effective monitoring technologies.